The discovery of the two types of small subunit ribosomal RNA gene in Eimeria mitis contests the existence of E. mivati as an independent species - Vrba, Vladimir; Poplstein, Martin; Pakandl, Michal (Veterinary parasitology, 2011)
Although the validity of the coccidian species, Eimeria mivati, has been questioned by many researchers for a long time there has not been any molecular analysis that would help resolve this issue. Here we report on the discovery of the two types of small ribosomal subunit (18S) gene within the Eimeria mitis genome that correspond to the known 18S sequences of E. mitis and E. mivati, and this is in conflict with the existence of E. mivati as an independent species. We have carried out five single oocyst isolations to obtain five single-oocyst-derived strains of E. mitis and these were analyzed by the sequencing of 18S and mitochondrial cytochrome c oxidase subunit I genes. The two types of 18S gene were found to be present in each strain in roughly equal ratios. This indicates that if the strains carrying only one or the other 18S type exist, they will likely cross-breed and still represent a single species. However, the more probable explanation is that all strains of E. mitis contain two types of 18S gene and that the occasional detection of only one or the other type by sequencing might be caused by insufficient sampling. This is also the first report of the two types of 18S gene in Eimeria, which has already been described in some other apicomplexan species, most notably Plasmodium. We also found that these two types of ribosomal RNA differ significantly in their secondary structure. The biological significance of the two 18S gene variants in E. mitis is not known, however, we hypothesize that these variants might be used in different stages of the parasite's life-cycle as it is in other apicomplexan species investigated so far.
Keywords: kur domácí; Animals; Base Sequence; Molecular Typing; RNA, Ribosomal, 18S; feces; Feces; Electron Transport Complex IV; protozoální vakcíny; Chickens; Protozoan Vaccines; Poultry Diseases; oocysty; Oocysts; Eimeria; Molecular Sequence Data; respirační komplex IV; nemoci drůbeže; molekulární typizace; RNA protozoální; kokcidióza; Coccidiosis; RNA, Protozoan; Ribosome Subunits, Small, Eukaryotic; Phylogeny; molekulární sekvence - údaje; malé podjednotky ribozomu eukaryotické; DNA, Protozoan; Czech Republic; protozoální DNA; RNA ribozomální 18S; sekvence nukleotidů; Vaccines, Attenuated; Sequence Analysis, DNA; Česká republika; sekvenční analýza DNA; zvířata; atenuované vakcíny; fylogeneze